The Impact of Tertiary Study on the Labour Market Outcomes of Low-qualified School Leavers - Sarah Tumen; Sarah Crichton; Sylvia Dixon (New Zealand Government, The Treasury, 2015)
This study examines the impacts of post-school education on the labour market outcomes of young people who leave school with few qualifications. Specifically, it estimates the effects of tertiary study on the employment rates, benefit receipt rates and earnings of young people who left school without completing NCEA level 2, who enrolled at a tertiary institution while they were aged 16–19. The benefits of the further education are measured by comparing the students' post-study outcomes with those of matched comparison groups of other poorly qualified school leavers who did not undertake any tertiary education. We find that enrolling in a level 1–3 or level 4 certificate programme had a small positive impact on the employment of low-qualified school leavers, raising their employment rate by 3.4 percentage points on average, two years after they ceased studying. However, the benefits of tertiary study were confined to the 44% of students who completed a qualification and were not experienced by non-completers. Students who completed a level 1–3 certificate were 8.5 percentage points more likely to be employed and 6.4 percentage points less likely to be receiving a benefit than their matched comparisons two years after finishing. Slightly larger benefits were experienced by those who completed a qualification at level 4 or higher. The size of the employment impacts associated with gaining a qualification varied by gender and ethnicity, the type of tertiary provider and the subject area of the qualification. There was no evidence that tertiary study had a significant impact on participants' level of earnings, after controlling for their employment status.
Keywords: I26; 330; Junge Arbeitskräfte; Bildungsabschluss; Hochschule; Absolventen; Qualifikation; Arbeitsmarktintegration; Neuseeland